Pelaksanaan Penilaian Harian (CekList) Pembelajaran Tahfidzul Qur’an di Taman Kanak-Kanak AnakQu Catur Tunggal Sleman Yogyakarta - Wulandari, Retno (ACIECE, 2019)
his study is a descriptive study that aims to describe the process of carrying out daily assessments on learning Tahfidzul Qur’an in AnakQu Kindergarten Sleman Yogyakarta. Data collection techniques are by interviewing, documenting and observing and analyzing data with data reduction flow, data display, and verification / conclusion. The result is that AnakQu Kindergarten Sleman Yogyakarta carry out daily assessments in the form of checklists and anecdotes in accordance with the 2013 curriculum which are then used as a reference point for what treatment should be given to students in the next learning process